2022
DOI: 10.1002/jqs.3434
|View full text |Cite
|
Sign up to set email alerts
|

Last Glacial Maximum active layer thickness in Western Europe, and the issue of ‘tundra gleys’ in loess sequences

Abstract: Late Marine Isotope Stage (MIS) 3 and MIS 2 loess-palaeosol sequences in Western Europe comprise alternating loess layer and 3-to 30-cm-thick bleached soil horizons with Fe-Mn oxide precipitations, which are usually interpreted as waterlogged active layers and referred to as 'tundra gleys'. Active layer thickness data derived from a regional climate model simulation and the fossils (shells, earthworm granules) found in 'tundra gleys' argue against such an assumption. Most of these horizons better correspond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…The LGM permafrost simulation by Stadelmaier et al 92 failed to reconstruct permafrost in the study area at a depth of −0.7 m. By contrast, Bertran et al, 93 using the same climate model but considering a representative ground level of −1.5 m, were able to reconstruct discontinuous permafrost in Hungary. Active layer thickness (ALT) was found to have ranged between 2 and 3 m in the region.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The LGM permafrost simulation by Stadelmaier et al 92 failed to reconstruct permafrost in the study area at a depth of −0.7 m. By contrast, Bertran et al, 93 using the same climate model but considering a representative ground level of −1.5 m, were able to reconstruct discontinuous permafrost in Hungary. Active layer thickness (ALT) was found to have ranged between 2 and 3 m in the region.…”
Section: Discussionmentioning
confidence: 77%
“…Temperatures >4 C suggest that the sampled area (the southern part of the Great Hungarian Plain) was not under permafrost during the LGM. However, the possibility that the coldest phases of the LGM were not captured by the analyses of aquifer NGTs should be kept in mind.The LGM permafrost simulation by Stadelmaier et al92 failed to reconstruct permafrost in the study area at a depth of À0.7 m. By contrast, Bertran et al,93 using the same climate model but considering a representative ground level of À1.5 m, were able to reconstruct discontinuous permafrost in Hungary. Active layer thickness (ALT) was found to have ranged between 2 and 3 m in the region.Together, this suggests strongly that (a) the area was close to the southern permafrost boundary and (b) the sand wedges developed within the active layer or in a context of deep seasonal frost (depending on local parameters).…”
mentioning
confidence: 79%
“…Nevertheless, the new ages provide important chronological controls on the presence of past permafrost in the Czech Republic, which have so far been completely lacking in previous attempts at empirical or model estimates of past permafrost extent across the European lowlands (cf. [3,8,11,16,19,[22][23][24][25][26][27][28][29][30]).…”
Section: Paleo-environmental Implicationsmentioning
confidence: 99%
“…Frost-weathering features and cryogenic carbonates in caves indicated that permafrost in and around the Bohemian and Most basins was at least 30-65 m thick at elevations <450 m asl [55,115] and model simulations suggested that its maximum thickness was 70-130 m [76,78]. The LGM active-layer thickness in lowland soils probably attained ~1-2 m [23,77]. Around this time, there were also the lowest MAGTs and MAATs inferred from borehole logs and former active-layer thickness, respectively, of ~−6°C to ~−4°C [75,76,117] and ~−7°C to ~−3°C [77], as well as a pronounced decline in noble gas recharge temperatures to values close to zero [118], which signal coldclimate conditions and the existence of permafrost.…”
Section: Older Permafrost Phase (~Last Glacial Maximum)mentioning
confidence: 99%
See 1 more Smart Citation